Analysis of the Influence of Profitability, Leverage, Company Size, and Financial Distress on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2024 - Tri Bowo Cahyono; Imronudin; Muzakar Isa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of profitability, leverage, company size, and financial distress on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2024. This study uses an explanatory quantitative approach to analyze the influence of profitability, leverage, company size, and financial distress on tax avoidance in manufacturing companies listed on the IDX in 2024. Secondary data in the form of financial reports of 101 manufacturing companies in 2024 were selected using purposive sampling. The analysis was conducted quantitatively using cross-sectional data and processed with E-Views 13 software. The results of this study are that profitability has a positive and significant effect on tax avoidance, leverage also has a positive and significant effect on tax avoidance, company size does not show a significant effect on tax avoidance, and financial distress has a positive and significant effect on tax avoidance